That's Not News: Audience Perceptions of "News-ness" and Why It Matters. Issue 5 (2nd September 2020) - Edgerly, Stephanie; Vraga, Emily K.
ABSTRACT: When is a tweet considered news? This study uses an experimental design to isolate two features of a headline shared on Twitter to determine the impact on audience ratings of 'news-ness.' We examine how people rate a Twitter post about potential government shutdown depending on: the type of story headline (breaking, exclusive, fact check, opinion), and the source of the story/tweet ( Associated Press, MSNBC, Fox News ). Results show that headline story type and source separately impact news-ness, with partisanship conditioning the influence of source on news-ness. Moreover, we find that ratings of news-ness mediate these effects on intent to verify tweet content, such that higher ratings of news-ness results in lower intent to verify. We argue that more attention needs to be paid to the central role that perceptions of news-ness plays in driving a range of outcomes in today's social media environment.